Morphology of the male terminalia of Aedes aegypti Linnaeus, the Yellow Fever Mosquito (Diptera: Culicidae). - Zaka-ur-Rab, Md. (Beiträge zur Entomologie = Contributions to Entomology, 1980)
Es wird die Morphologie der männlichen Genitalien von Aedes aegypti Linnaeus beschrieben.